ANALISIS PENGENDALIAN PENGADAAN BARANG BERGERAK DALAM MENINGKATKAN EFISIENSI ANGGARAN BELANJA DAERAH OLEH BAGIAN UMUM PADA SEKRETARIAT DAERAH KABUPATEN TAPANULI TENGAH* - German Sitompul (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This research includes three points to be analyzed: 1) the implementation of movable goods procurement , 2) the obstacles in conducting the movable goods procurement, and 3) the efforts taken to overcome the obstacles in conducting the movable goods procurement. The researcher finds out several obstacles in conducting the movable goods procurement, such as: unoptimized procurement standard for movable goods, dwindling personnels' attitude towards jobaccomplishment, and lacking delegation of authority to in decision making.The result shows that the movable goods procurement control in improving the efficiency of Local Revenue and Expenditure Budget at the Section of General Affairs of Tapanuli Tengah Local Secretariat has insufficiently been conducted. This condition is due to the following impediments: 1) unoptimized work performance of the personnels within the Section of GeneralAffairs of Tapanuli Tengah Local Secretariat, 2) controlling standard not systematically meeting the principles of related effective regulations, 3) dwindling personnels' attitude towards job accomplishment, 4) dual functions as the service-oriented and profit-oriented governmental organization, 5) organizational policies restraining the efficiency in controlling the movable goods procurement.